Abundance of Proboscis Monkey (Nasalis larvatus) at Samunsam Wildlife Sanctuary, Sarawak, Malaysia - Mohamad Abid, Kamaruzzaman (Universiti Malaysia Sarawak (UNIMAS), 2015)
A total two weeks on boat survey was conducted in October 2014 and February/March 2015 at Samunsam Wildlife Sanctuary. The purposes of this research to valid the abundance of proboscis monkey (Nasalis larvatus) with comparison of total abundance from previous studies on the same methodological mechanism. During the survey the groups of proboscis monkey sighted mainly were live at 2 km stretch further upstream from the river mouth of sanctuary's headquarter along Samunsam River. The abundance calculated for both periods were not much distinctive with 0.32 groups/km surveyed in October 2014 and a bit lower in February/March 2015 with 0.29 groups/km surveyed. Thus, with an average 0.305 groups/km surveyed in present study, the total abundance was much higher than two previous study conducted in 2001 and 2004. This is because the groups of proboscis monkey sighted were favoring their sleeping sites and have sufficient food availabilities in Samunsam area. The surveys also found that proboscis monkey tend to use trees from Rhizophora sp. and Avicennia sp. as their foraging site as well as for sleeping site.